Destiny and deliberation essays in philosophical theology - Kvanvig, Jonathan L. (Oxford : Oxford University Press, 2011)
Jonathan Kvanvig presents and defends a new theistic outlook - 'Philosophical Arminianism' - which reconciles a traditional high conception of deity with a conception of human beings as free and morally responsible. He offers an account of eschatological matters and divine deliberation and creation.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Theology; Religion -- Philosophy; Eschatology; Theism; Creation